Multi-functional nanomaterials and their emerging applications - Pandikumar, Alagarsamy; Ming, Huang Nay; Jothilakshmi, Rajendran (Materials science forum, 2014)
The multi-functional properties of nanomaterials offer a wide range of opportunities for addressing several research and development challenges in the area of nanoscience and nanotechnology. Multi-functional nanomaterials find wide application in a variety of sectors including agriculture, medicine, telecommunications, disaster management and environmental conservation. The focus of this special topic volume is on multifunctional nanomaterial development and their emerging applications towards commercialization. This special topic illustrates a new pathway to achieve novel practical application.